Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di Perusahaan Pertambangan: Review Literatur - Putri Maimunah; Supriati Munthe; Akmal Fiqi Ranu Mahendra; Hifza Haridani; Sri Hajijah Purba (Journal of Educational Innovation and Public Health, 2024)
Mining is a crucial sector in the global economy, yet it faces high risks and serious potential hazards for workers. According to statistical data from the Ministry of Energy and Mineral Resources, the number of mining accidents in 2023 increased significantly compared to 2021 and previous years, totaling 217 incidents. Therefore, the effective implementation of occupational health and safety management systems (OHSMS) is necessary to protect worker safety and health. The purpose of this writing is to review the implementation of occupational health and safety management systems (OHSMS) in mining companies, covering policy establishment, K3 planning, K3 plan execution, K3 performance monitoring and evaluation, as well as review and enhancement of OHSMS performance. This review employs a Literature Study method, sourcing data and articles from Google Scholar, PubMed, and ScienceDirect. Based on the literature study, the analysis of Occupational Health and Safety Management System implementation reveals that, on average, mining companies have their own policies established. Regarding K3 planning, each company has its own K3 planning strategy. However, the execution of K3 plans shows varying levels of implementation across different companies. In terms of performance monitoring and evaluation, companies assess K3 performance using specific indicators and undertake necessary improvements. Finally, review and performance enhancement efforts are undertaken for continuous improvement.